Prolactinoma or leiomyoma-associated hyperprolactinemia—this is the question, a case report and review of the literature - Ralitsa Robeva; Radina Ivanova; Teodora Kamenova; Atanaska Elenkova; Sabina Zacharieva (Clinical and Experimental Obstetrics & Gynecology)
Background: Hyperprolactinemia is a common finding in women of reproductive age that could result from physiological factors, pathological conditions or the use of different medications. The therapeutic approach depends on the etiology of hyperprolactinemia, thus, the proper diagnosis is paramount. Case: Herein, we present a case of a young woman with pituitary incidentaloma and leiomyoma-associated hyperprolactinemia. The initial diagnosis was microprolactinoma, based on typical clinical features, increased prolactin levels, and pituitary adenoma. However, dopamine agonist treatment did not lead to any reduction of prolactin levels or clinical improvement. The patient was myomectomized because of uterine fibroid enlargement. After the surgery, the hyperprolactinemia resolved completely, while the pituitary adenoma did not show any changes. The concomitant development of pituitary adenoma and extrapituitary hyperprolactinemia might not be such a rare phenomenon, considering the high prevalence of pituitary incidentalomas. Conclusions: Currently, there are no specific tests that could distinguish pituitary from extrapituitary prolactin production. Our case report and the literature review show that leiomyoma-associated hyperprolactinemia should be considered in women of reproductive age with treatment-resistant prolactinoma and uterine fibroids above 5 cm. Further studies are needed to explore the underlying mechanisms and the possible regulators of the ectopic prolactin secretion.